2019
DOI: 10.19136/era.a6n17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Varroosis en abejas melíferas en diferentes condiciones ambientales y regionales de Jalisco, México

Abstract: RESUMEN. El objetivo fue determinar la prevalencia de Varroa destructor, el grado de infestación del ácaro y la relación del parásito con variables geográficas y climáticas en 369 colonias de abejas Apis mellifera de nueve municipios de zonas templadas y cálidas del estado de Jalisco, México. Se encontró una prevalencia promedio de 88% y nivel de infestación de 5.2% del parásito, con diferencias significativas entre municipios para estos parámetros (p < 0.05), pero sin diferencias entre zonas climáticas. La pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
1
2
3
1
Order By: Relevance
“…The climate type had an effect on the prevalence of Varroa. This result is different from the results of other studies [41,57], but is similar to the result of Medina et al (2014) [40], who also found an effect of the climate type on the prevalence of Varroa.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…The climate type had an effect on the prevalence of Varroa. This result is different from the results of other studies [41,57], but is similar to the result of Medina et al (2014) [40], who also found an effect of the climate type on the prevalence of Varroa.…”
Section: Discussioncontrasting
confidence: 95%
“…Medina et al (2014) [40] found that prevalence was higher in the temperate sub-humid climate (21 The climate type had an effect on the infestation levels of Varroa. This result is different from what was reported in other studies [41,57], but is similar to the results of other studies that also found an effect of the climate type on the infestation levels of Varroa in the colonies [37,40].…”
Section: Discussioncontrasting
confidence: 70%
“…The presence of the Varroa destructor mite is the main vector of these pathological processes 11,12 . This infestation caused by an ectoparasitic mite [13][14][15] is distributed in most countries of the world 16 and is the one that most concerns beekeepers 3,13,14 . Currently in Mexico, the presence of varroasis has been reported in all states 7,[13][14][15]17 , the state of Veracruz presented the first report of identification in the 1990s 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies conducted at the state or local levels have shown similar or slightly lower V. destructor prevalence in honey bee colonies. For example, in the southern area of Jalisco state, which is part of the Pacific Coast region, V. destructor was diagnosed in 88% of the sampled apiaries [46]. Another state-level survey conducted in Zacatecas also reported a frequency of 88% varroa mite-positive colonies [6].…”
Section: Discussionmentioning
confidence: 99%